1991
DOI: 10.1113/jphysiol.1991.sp018889
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phorbol ester on contraction, intracellular pH and intracellular Ca2+ in isolated mammalian ventricular myocytes.

Abstract: SUMMARY1. We have investigated the actions of certain phorbol esters on the intracellular pH, intracellular Ca2+ and contractility of isolated rat and guinea-pig cardiac myocytes. Intracellular pH was measured using 2',7'-bis(carboxyethyl)-5(6)-carboxyfluorescein (BCECF) and intracellular Ca2+ was measured using Fura-2.2. Application of the phorbol ester 12-0-tetradecanoylphorbol 13-acetate (also called phorbol 12-myristate 13-acetate) (TPA) (which activates protein kinase C) to rat cardiac myocytes significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 47 publications
1
35
0
Order By: Relevance
“…It is well established that the effects of the vasoactive peptides ET-1 and angiotensin II may vary with the preparation which is studied and with the stage of development. In intact isolated heart preparations, both positive and negative inotropic effects of ET-1 and angiotensin II have been reported in adult rabbits and rat hearts (10,11,16,29,33). These conflicting responses may be related to the effects of these vasoactive peptides on coronary vasomotor tone, thus confounding the assessment of direct myocardial actions.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is well established that the effects of the vasoactive peptides ET-1 and angiotensin II may vary with the preparation which is studied and with the stage of development. In intact isolated heart preparations, both positive and negative inotropic effects of ET-1 and angiotensin II have been reported in adult rabbits and rat hearts (10,11,16,29,33). These conflicting responses may be related to the effects of these vasoactive peptides on coronary vasomotor tone, thus confounding the assessment of direct myocardial actions.…”
Section: Discussionmentioning
confidence: 98%
“…In the present experiments, ET-1 and angiotensin II failed to cause intracellular alkalinization in the presence of a selective protein kinase C inhibitor in normal cells. MacLeod and Harding (29) have reported previously that the recovery from an acute acid load in isolated rat myocytes is partially inhibited by amiloride or by removing extracellular Na ϩ . They observed that exposure to phorbol ester 12-myristate 13-acetate (which activates protein kinase C) exaggerated the changes in intracellular pH and associated changes in cell shortening in normal rat and guinea pig myocytes in response to NH 4 Cl challenge, which suggests the stimulation of Na ϩ -H ϩ exchange.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PMA stimulates sarcolemmal NHE of isolated ventricular myocytes. 36 To rule out an effect of NHE in the observed PMA-induced increase of AEfl activity, anion exchange assays were repeated under conditions where NHE was fully blocked (amiloride, 1 mmol/L). In the presence of amiloride, steady-state pH i decreased slightly after PMA addition (7.29Ϯ0.03 and 7.23Ϯ0.01 before and after PMA, respectively, nϭ3), but NHE blockade did not affect the PMAinduced increase of AE3fl activity, 2.6Ϯ0.1 and 3.8Ϯ0.2 mmol/L · min Ϫ1 , before and after PMA, respectively (48Ϯ3% of increase, nϭ3, PϽ0.05).…”
Section: Identification Of the Pkc-sensitive Ae Isoformmentioning
confidence: 99%
“…Experiments were performed on single left ventricular myocytes isolated from adult male guinea pigs (550-750 g) by enzymatic digestion as previously described (MacLeod & Harding, 1991). We chose to study male, rather than female, animals to avoid the potential problems associated with varying expression of the ER that occurs throughout the oestrus cycle.…”
Section: Cell Isolation and Indo-1 Loadingmentioning
confidence: 99%